The development of a 3-Pass Persistent Scatterer algorithm using the Integer Ambiguity Search method - Warren, Mark (2007)
Differential interferometric synthetic aperture radar (InSAR) is a well used technique for measuring deformations, but often suffers greatly from effects due to atmospheric differences occurring between different SAR images. Recently a new set of techniques have been developed called Persistent Scatterer techniques, which take advantage of the high number of SAR images available to try and model out the atmospheric effects. To aid this process, all present techniques make use of a Digital Elevation Model (DEM) to remove the interferometric phase due to topography, but as a consequence this contaminates the phase values with an unknown error due to the DEM, which has to be modelled out in the processing chain. In this thesis a new Persistent Scatterer (PS) method is proposed that does not use a DEM to remove the topographic phase component, but rather one of the interferograms used in the study, and hence does not need to calculate topographic height corrections. This is achieved by using the Integer Ambiguity Search (IAS) 3-Pass differential technique. The developed algorithms are then tested and assessed over two test sites in central London, UK.